Detection of human immunodeficiency virus (HIV) RNA in the sweat of HIV-infected patients - Fatih Mehmet Hanege; Fatma Sargin; Servet Karaca; Oguz K. Egilmez; Haluk Vahaboglu; M. Tayyar Kalcioglu (İstanbul Kuzey Klinikleri, 2020)
OBJECTIVE: Human immunodeficiency virus (HIV) infection is a significant health problem. Many studies reported that HIV was mainly transmitted through parenteral exposure, sexual activity, and body secretions, such as saliva and semen. Many people, including health-care providers and patient relatives, may easily contact with the sweat of HIV-infected patients. Although reference books assert that HIV does not transmit through sweat, to our knowledge, there is no systemic study which this statement is based upon. This study aims to investigate the potential of sweat to transmit HIV infection. METHODS: This study included 31 treatment-naive HIV RNA-positive patients who were in the acute phase of the infection and 26 subjects with a negative HIV RNA test who had received antiviral treatment. A total of 57 sweat samples collected from intact skin areas were prospectively evaluated by polymerase chain reaction (PCR) for the presence of HIV RNA. HIV RNA levels in the blood samples were also noted. RESULTS: HIV RNA was not detected by PCR in any sweat sample taken from HIV-infected HIV RNA-negative and -positive subjects. CONCLUSION: The findings obtained in this study suggest that sweat by itself has no potential for transmitting HIV infection.